Creation and salvation dialogue on Abraham Kuyper's legacy for contemporary ecotheology - Conradie, Ernst M. (Studies in Reformed Theology, 2011)
This volume explores the legacy of the Dutch theologian and statesman Abraham Kuyper for contemporary Christian ecotheology. A crucial problem in ecotheology is how to do justice to both creation and salvation as acts of God, given the impact of the environmental crisis and the concern for creation (as creatura). Can Kuyper help one in this regard, given his controversial legacy, especially in South Africa? The volume explores Kuyper's notions of revelation, common grace and re-creation on this basis. It is structured as an inter-continental dialogue with a set of essays by Ernst Conradie, responses from Clifford Anderson, Vincent Bacote, Hans Engdahl, Dirk van Keulen, Cornelis van der Kooi, Benjamin Myers, Leslie van Rooi and Günter Thomas, and a rejoinder.